Evaluation of the Effectiveness of Lecturer Development Programs in the Context of Higher Education Management - Saryanto Saryanto; Abdul Sahib; Ita Soegiarto; Musmulyadin Musmulyadin; Rahayu Retnaningsih (Yayasan Adra Karima Hubbi, 2024)
Background. Lecturer development is one of the right strategies in improving the quality of higher education. Purpose. However, evaluating the effectiveness of lecturer development programs is still an important concern in the context of higher education management to ensure their success and relevance. Method. This research aims to evaluate the effectiveness of lecturer development programs in the context of higher education management, with a focus on achieving goals, participant satisfaction, and its impact on lecturer performance. A mixed approach was used in this research, with a combination of quantitative and qualitative analysis. Data was collected through surveys with lecturers participating in the development program and in-depth interviews with development staff and related lecturers. Results. The results of the analysis show that the majority of lecturers participating in the development program felt that the program was effective in improving their competence. However, there was variation in levels of satisfaction and perceived effectiveness between participants. Additionally, the impact of development programs on lecturer performance also varies, with some lecturers reporting significant improvements while others do not. Thorough evaluation of faculty development programs is critical to ensuring effective investment in higher education resources. Although most lecturers found the program useful, there were challenges in maintaining the program's consistency and relevance. Conclusion. Therefore, continuous improvement in the design, implementation and evaluation of lecturer development programs is needed to support continuous improvement in the quality of higher education. Hopefully this research can become a reference for future researchers in conducting research related to this field of research.